The Ambivalence of the Nemo Plus Juris Principle in the Validity of Land Transactions in the Digital Verification System - Amrullah; Megawati Barthos (Indonesian Journal Publisher, 2026)
The digitalization of land administration has driven fundamental changes in how the validity of land rights transactions is understood and applied in legal practice. The implementation of electronic certificates, database integration, and digital verification mechanisms has strengthened public reliance on the registration system as a source of administrative legitimacy. This development has given rise to normative ambivalence regarding the principle of nemo plus juris, which classically asserts that a person cannot transfer rights beyond what they own. When system data becomes the primary reference for verification, tension arises between the substantive truth of ownership and the administrative validity based on digital registration. This study aims to analyze the paradigm shift in the validity of land transactions in the digital era and formulate a conceptual reconstruction that balances the protection of original owners with the need to maintain legal certainty and transaction stability. The method employed is normative legal research with a limited statutory, conceptual, and comparative approach, through an analysis of the Basic Agrarian Law, Government Regulations on Land Registration, electronic certificate regulations, and electronic system provisions. The results reveal a dualism in validity between substantive and systemic aspects, which has the potential to create legal uncertainty if not clearly regulated. Reliance on digital systems broadens the meaning of legal legitimacy, but also presents the risk of systemic error and an incompletely defined distribution of responsibility. Reconstruction of the validity model is necessary through a reinterpretation of the nemo plus juris principle that adapts to technology, the establishment of digital verification-based due diligence standards, and the development of a legal protection model based on risk allocation. This approach is expected to strike a balance between the efficiency of digitalization and the protection of substantive ownership rights in the modern land system.